(untitled) (Modern education and development, 2025)
This article investigates the integration of speaking and listening skills through task-based activities in EFL classrooms, with a particular focus on the context of Uzbekistan. The study highlights how interactive tasks—such as role-plays, problem-solving exercises, and information-gap activities—promote real-time communication and enhance learners’ fluency, comprehension, and confidence. The research draws on classroom-based practices and aligns with contemporary language teaching methodologies that emphasize communicative competence. The paper also discusses the pedagogical implications of applying task-based learning within Uzbekistan’s multilingual and exam-oriented education system.